P087 Impact of coil waveform and orientation on TMS evoked potentials. A TMS-EEG study. Issue 3 (March 2017) - Pisoni, A.; Mattavelli, G.; Vergallito, A.; Rosanova, M.; Fecchio, M.; Romero Lauro, L.J.
Abstract : Intro: Mono and biphasic TMS pulses and coil orientation have been consistently found to produce different outcomes in terms of cortical and cortico-spinal outputs. Knowing how these TMS parameters affect the evoked cortical response becomes even more crucial when TMS is coupled with EEG, since it is necessary to elicit a reliable cortical response minimizing the stimulator intensity, in order to reduce muscle or magnetic artefacts. Aims: Here, we investigated the impact of different coil orientations and biphasic vs monophasic pulses on prefrontal TMS Evoked Potentials recorded from a HD EEG system. We aimed at determining which cortical response were evoked from different waveforms and orientations, as well as which coil was more suitable for TMS-EEG studies. Methods: Ten healthy subjects took part in the experiment, in which 4 different TMS-EEG recordings were performed. TMS was applied over the right DLPFC, changing coil waveform and direction: monophasic and biphasic coils were oriented antero-posteriorly, i.e. perpendicular to the stimulated gyrus, or latero-dorsally, i.e. parallel to the target gyrus. EEG was concurrently recorded from 60 electrodes. TMS stimulator output was adjusted individually to reach a current density at the hotspot of 95 V/m 2 . Results: Preliminary results (7 ss) indicate a different effect of coil orientation for the two waveforms. Biphasic coils elicited greater TEPs than monophasic ones. Concerning TEP components, for the biphasic coil the parallel orientation evoked greater early components (Fig. 1 ), which reflect cortical excitability properties of the underlying cortex, when compared to the perpendicular direction. Conversely, monophasic pulses when oriented perpendicularly to the stimulated gyrus, elicited a greater N100 (Fig. 2 ), which is a reliable TEP component linked to GABAb-mediated inhibitory processes. Conclusion: Since the biphasic waveform elicited greater TEPs at a lower output, this kind of coil might be more suitable for TMS-EEG studies: stimulating at lower intensities, indeed, means evoking less TMS- related artifacts. Moreover different waveforms seem to trigger different neural responses: biphasic pulses are more suitable for testing cortical excitability, while monophasic ones perpendicularly oriented are better to highlight inhibitory processes.